First outcome results after total knee and hip replacement from the Lithuanian arthroplasty register - Šarūnas Tarasevičius; Algimantas Čebatorius; Rasa Valavičienė; Justinas Stučinskas; Linas Leonas; Otto Robertsson (Medicina, 2014)
Background and objective: In 2010, the Lithuanian Association of Arhtroplasty was established and on January 1, 2011, initiated a national study of all reoperations after total knee (TKR) and total hip replacement (THR) in Lithuania. The aim of the study was to investigate the revision rates after TKR and THR at two years follow-up. Materials and methods: Lithuanian patients undergoing primary TKR and THR from January 1, 2011, to December 31, 2012, were included in the study. The patient, surgery and prosthetic implantation data were collected via internet database. For reoperations we recorded the reason and type of revision, primary implantation date. We analyzed implant survival rates using any revision as an endpoint on included primary procedures, performed until September 1, 2013. Results: The completeness of the register verified with state patients fund data reached 85% of all replacements. Out of 3823 primary TKR during the study period 25 revisions were performed with overall implant survival rate 99%. The main reason for knee revision was infections. During the inclusion period we registered 6072 primary THR and 149 revisions with overall implant survival rate 97%. Recurrent dislocation of prosthetic component was the main reason for hip revision. Significantly inferior survival results for femoral neck fracture patients were observed as compared with patients operated for osteoarthritis. Posterior approach as compared to others significantly affected inferior implant survival rates for femoral neck fracture patients. Conclusions: The overall survival after total knee and hip replacements revealed a high treatment quality of this surgery in Lithuania.